(3JaSjQ GTJbGb CSeGA Gddg YR hLds - (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe, (B337 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdMb GdeHjf gPG cJGH CaQOJg dTQM GTJbGb CSeGA Gddg YR hLd s
(3BNQgG (B:s
(3agPG ePgH GdYdeGA ai Pdc hGddg CYde hCMce hgPG BNQ Gdbhd ai GTJbGb CSeGA Gddg YR hLd hUaGJg s
(3QhGjI CHh HcQ CMeO Hf eMeO Hf SedI GdZSGfi GdeYQha HGHf TQGe HBNQg bQGAI dYd Hf GdMSf GHf Ydi GdQHYi Ydi QhGi GdcJGH GdePchQ SfI (B434s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3GMRGH hCOYjI (B46) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs